2009
DOI: 10.1021/ml900009d
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Potent and Orally Bioavailable CCR2 and CCR5 Dual Antagonist

Abstract: This report describes the discovery of a potent, orally bioavailable CC chemokine receptor 2 (CCR2) antagonist which, while optimized for CCR2 potency, also had potent CC chemokine receptor 5 (CCR5) activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…It is worth noting that a number of small-molecule CCR2 antagonists reported in the literature also bind to CCR5 with a range of relative affinities. 30,31 …”
Section: In Vitro Pharmacologymentioning
confidence: 99%
“…It is worth noting that a number of small-molecule CCR2 antagonists reported in the literature also bind to CCR5 with a range of relative affinities. 30,31 …”
Section: In Vitro Pharmacologymentioning
confidence: 99%
“…It is worth noticing that most CCR2 antagonists reported in the literature also bind to the closely related receptor CCR5 [76]. CCL5 is upregulated in rat and mouse models of nephrotoxic serum nephritis and mouse models of lupus nephritis [77].…”
Section: Chemokine Receptorsmentioning
confidence: 99%
“…However, the combination of CXCL12 (homeostatic chemokine) and CCL2 (inflammatory chemokine) blockade prevented proteinuria in mice with diabetic nephropathy [84]. With this idea, recent studies have used a dual antagonist to target both CCR2 and CCR5 [76,85,86] although none of them have been tested in clinical studies yet. The difficulty in targeting these receptors is due to both the complexity of unraveling their structure and to the functional redundancy of the chemokine system and the formation of homo-and hetero-oligomers between different chemokines and chemokines receptors.…”
Section: Chemokine Receptorsmentioning
confidence: 99%
“…More recently it has been suggested that dual specificity antagonists targeting both CCR2 and CCR5 receptors offer some advantages in the treatment of diseases such as atherosclerosis [6]. Several companies have shown an interest in such agents with Merck describing the identification of the compound (1) [7], Eli Lilly the metabolic effects of LYSN-2238290 [8], Bristol-Myers Squibb the activity of BMS-A in models of autoimmune disease [9], Novartis describing compounds such as NIBR-803 [10], Rapid Pharma the activity of RAP-103 in neuropathic pain [11], while Tobira Therapeutics' cenicriviroc (TBR-652) is in Phase II development for the treatment of HIV infection [12]. Incyte and Pfizer recently described the identification of INCB-10820/PF-4178903, from a collaboration established in 2005 to identify CCR2 antagonists, and its selection as a clinical candidate [13].…”
Section: Introductionmentioning
confidence: 99%